Birtingarmynd heilabilunar í vistunarmati aldraðra fyrir hjúkrunarrými 1992-2001 - Oddur Helgason; Thor Aspelund; Pálmi V. Jónsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2004)
Objective: Dementia is a growing health issue and is currently the main reason for nursing home (NH) admission. The objective of this study is to describe the elderly who qualified for an admission to NH in the Reykjavík metropolitan area. Special attention is paid to the degree of dementia and how it affects various factors such as: waiting time for NH admission, factors that could possibly predict survival after preadmission nursing home assessment (PNHA) and survival in NH?s. Material and methods: Every PNHA evaluation is stored in a database by SKYRR Inc. Information from that database regarding all, who lived in the Reykjavík metropolitan area and had undergone their first PNHA during the period from January 1st 1992 to 31st of December 2001, was collected. Information about survival was collected from the Icelandic National Registry. There were 3417 individuals in the study group. SPSS was used for statistical analysis. Results: Dementia is a major risk factor for NH admission with about 79% of the elderly with some degree of dementia. Dementia correlated with lower age at admission for men, p<0,01. The degree of dementia had no effect on the age of women at admission. The total score of the PNHA correlated with higher degree of dementia. Higher dementia degree meant less survival for men after NH admission, p=0,02. The degree of dementia did not effect survival of women after admission. The death rate was highest in the first year after PNHA for all degrees of dementia. The ratio of men who were still alive after 3 years was 30% but 46% of the women were still alive, p<0,01. Factors predicting longer survival were lower age and good mobility for both sexes. In men with high or very high degree of dementia a high score for behavioral symptoms predicted shortened survival. Conclusions: Dementia is the main reason for NH admission in Iceland and therefore special attention must be paid to it when NH beds are assigned. The priority of males should be revised so that men with higher degree of dementia be ...